2018
DOI: 10.1021/acssynbio.8b00216
|View full text |Cite
|
Sign up to set email alerts
|

Transcription Driven by Reversible Photocontrol of Hyperstable G-Quadruplexes

Abstract: G-quadruplexes occur in promoter regions, 5′-untranslated regions of mRNA and telomeric regions, and they function as regulatory elements for various key biological events, such as transcription, translation, and telomere elongation. As the stability of G-quadruplexes dramatically impacts these biological processes, controlling G-quadruplex stability via external stimuli such as light enables regulation of important biological phenomena with high spatial and temporal resolution. Here, we report a method for re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 44 publications
0
21
0
Order By: Relevance
“…By incorporation into a DNA promoter, azobenzenes controlled cell-free transcription [ 48 ] and gene expression [ 49 ], using UV or blue light as a stimulus. Incorporation of photoswitchable nucleobases into a G4 sequence of a promoter allowed for controlled expression of a reporter protein in zebrafish [ 50 ]. Reversible strategies for translation were also developed by capping the 5′ end of the mRNA with azobenzene or styryl photoswitches [ 50 , 51 ].…”
Section: Light-controlled Gene Expression Using Nucleic Acidsmentioning
confidence: 99%
See 1 more Smart Citation
“…By incorporation into a DNA promoter, azobenzenes controlled cell-free transcription [ 48 ] and gene expression [ 49 ], using UV or blue light as a stimulus. Incorporation of photoswitchable nucleobases into a G4 sequence of a promoter allowed for controlled expression of a reporter protein in zebrafish [ 50 ]. Reversible strategies for translation were also developed by capping the 5′ end of the mRNA with azobenzene or styryl photoswitches [ 50 , 51 ].…”
Section: Light-controlled Gene Expression Using Nucleic Acidsmentioning
confidence: 99%
“…Incorporation of photoswitchable nucleobases into a G4 sequence of a promoter allowed for controlled expression of a reporter protein in zebrafish [ 50 ]. Reversible strategies for translation were also developed by capping the 5′ end of the mRNA with azobenzene or styryl photoswitches [ 50 , 51 ]. UV light inhibited the recruitment of a translation initiation factor, while blue light activated recruitment and expression to control differentiation in mammalian cells and zebrafish.…”
Section: Light-controlled Gene Expression Using Nucleic Acidsmentioning
confidence: 99%
“…Despite great progress in recent years, the biological roles of the different epigenetic modifications are not yet fully understood 117. On the other hand, there is a challenging opportunity to introduce some non-canonical modifications to DNA to explore their possible use in regulation of gene expression 1823. We have reported a study of transcription of DNA templates bearing different non-natural modifications in the major groove by bacterial RNAPs and found that bulkier modifications inhibited transcription whereas some small modifications were tolerated and the modified DNA templates were still transcribed into RNA 24.…”
mentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17] On the other hand, there is a challenging opportunity to introduce some non-canonical modications to DNA to explore their possible use in regulation of gene expression. [18][19][20][21][22][23] We have reported a study of transcription of DNA templates bearing different non-natural modications in the major groove by bacterial RNAPs and found that bulkier modications inhibited transcription whereas some small modications were tolerated and the modied DNA templates were still transcribed into RNA. 24 We also found that DNA templates containing 5-hydroxymethyluracil (U hm ), a rare natural base whose biological role is yet unknown, [25][26][27][28] can enhance (up to 3.5 times) transcription depending on the promoter.…”
mentioning
confidence: 99%
“…35,36 Guanine analogues carrying arylvinyl moieties synthesized by Ogasawara and coworkers have also been used to reversibly photoregulate DNA duplex or G-quadruplex formation. 37,38 Our group has developed photoresponsive DNA and RNA by introducing azobenzene via D-threoninol or other acyclic diols into oligonucleotides. 39 Despite the great applicability of XNAs, photoregulation of the XNA duplex has not yet been achieved.…”
mentioning
confidence: 99%